Compound Formation in Language Mixing - Alexiadou, Artemis (Frontiers in Psychology, 2020)
There is a growing body of literature using the tools of syntactic models of word formation (e.g. Distributed Morphology) to provide analyses of language mixing phenomena, in particular word internal mixing. In fact, the very phenomenon of word internal mixing directly supports a syntactic approach to word formation, according to which words are structurally complex. On the basis of this view, the basic units of word formation involve roots that combine with functional elements in the syntax. The combination of roots with functional elements creates words. This paper is in line with this work and investigates further the question of how word formation operates in cases of language mixing and what exactly is being mixed in mixing, i.e. words vs. roots. After reviewing literature on word internal mixing, I will discuss compound formation in language contact situations, the question being of how compounding in mixing can inform both theories of mixing and theories of word-hood. Compounding is important to answer the question of what exactly is being mixed in mixing, as language differ with respect to the units they employ for compound formation, i.e. words vs. roots and to the availability of linking elements to form compounds. Moreover, compounding is important to understand the role the two languages play in mixing, as languages differ with respect to head-ness (left or right) of their compounds. The data to be discussed will be a mixture of materials that have already been published in the literature and newly collected data and involve several mixing varieties, namely Greek-English, Greek-German, Greek-Turkish, Turkish-Norwegian, Turkish-Dutch and French-Dutch.